Handbook on first aid, rescue & water supply - Vicente, Jezreel B.; Vicente, Rhescien Mae B.; De Asis, Maria Krisia Fae R. (Quezon City Wiseman's Book Trading, Inc., 2015)
"This textbook is designed for the use of persons who are responsible for giving emergency care to the sick and injured. It provides essential information in developing the functional first aid capabilities required by the police, firemen, rescuers, paramedical personnel, and ambulant attendants. Emergency care instruction extending beyond the information given in this book should be provided by physicians and other specialized personnel.
Includes bibliographical references.
Keywords: First aid in illness and injury -- Handbooks, manuals, etc; Emergency medicine -- Handbooks, manuals, etc; Rescue work